2015
DOI: 10.1073/pnas.1423673112
|View full text |Cite
|
Sign up to set email alerts
|

fMRI of the rod scotoma elucidates cortical rod pathways and implications for lesion measurements

Abstract: Are silencing, ectopic shifts, and receptive field (RF) scaling in cortical scotoma projection zones (SPZs) the result of long-term reorganization (plasticity) or short-term adaptation? Electrophysiological studies of SPZs after retinal lesions in animal models remain controversial, because they are unable to conclusively answer this question because of limitations of the methodology. Here, we used functional MRI (fMRI) visual field mapping through population RF (pRF) modeling with moving bar stimuli under pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 56 publications
(103 reference statements)
6
39
0
1
Order By: Relevance
“…Some authors have suggested the use of an artificial scotoma to mimic the patients' visual field extent, to help elucidate the origin of remapping (Goesaert et al, 2014, Masuda et al, 2010). Previous works applying central artificial scotomata in healthy participants (Barton and Brewer, 2015, Baseler et al, 2011b, Haak et al, 2012) reported a visual cortical remapping similar to the effects usually seen in patients. Given that we did not use this approach, two possible explanations remain possible to explain functional remapping in our group of patients: fast adaptation or long term reorganization mechanisms.…”
Section: Discussionsupporting
confidence: 66%
“…Some authors have suggested the use of an artificial scotoma to mimic the patients' visual field extent, to help elucidate the origin of remapping (Goesaert et al, 2014, Masuda et al, 2010). Previous works applying central artificial scotomata in healthy participants (Barton and Brewer, 2015, Baseler et al, 2011b, Haak et al, 2012) reported a visual cortical remapping similar to the effects usually seen in patients. Given that we did not use this approach, two possible explanations remain possible to explain functional remapping in our group of patients: fast adaptation or long term reorganization mechanisms.…”
Section: Discussionsupporting
confidence: 66%
“…In response to the AS, pRFs shift their preferred spatial position towards the AS border. While such shifts have been reported previously for pRFs initially located inside the natural SPZ (31) and ASPZ (1012, 32), our study is the first to show that this reconfiguration is not restricted to the ASPZ, but is a system-wide phenomenon. Within the ASPZ, the pRFs shifted their preferred position towards the AS border, which could be consistent with an extrapolation process.…”
Section: Discussionsupporting
confidence: 66%
“…Der Vergleich der Patientendaten mit denen von Kontrollen mit simuliertem Skotom zeigt, dass die beobachtete Aktivität nicht durch Plastizität, sondern mit dem Auftreten von kortikalen Neuronen mit ektopen rezeptiven Feldern auch im Normalfall mit simuliertem Zentralskotom assoziiert ist. Dies zeigt, wie wichtig es ist, Patientendaten mit adäquaten Kontrollen zu vergleichen, wie auch eine aktuelle Studie zum skotopischen Zentralskotom unterstreicht [26].…”
Section: Kortikale Organisation Bei Erworbener Und Kongenitaler Foveaunclassified